Developing Educational Animation on Food Additives for Young Learners Using the 4D Model - Ria Chandra Kartika; Yoswenita Susindra; Lisus Setyowati; Malinda Capri Nurul Satya (International Journal of Healthcare and Information Technology, 2026)
Modern dietary patterns have increased children’s consumption of processed foods containing food additives, namely preservatives, flavor enhancers, sweeteners, and colorants (4Ps), which may increase the risk of degenerative diseases in the future. Although many studies discuss unhealthy food consumption among children, limited educational media specifically address food additives in a form that is engaging and suitable for elementary school students. This study aimed to fill this gap by developing an animated educational video on 4P foods as an innovative medium for school-based health promotion. This study used a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate) and applied a pre-test–post-test design to evaluate its effectiveness. The developed animation was validated by media and material experts and then tested on 23 elementary school students to assess feasibility, acceptance, and knowledge improvement. The results showed that the animation was highly feasible and well accepted by students. Students reported that the video was interesting, easy to understand, and helpful in learning about healthy food choices. After watching the video, students’ knowledge about food additives increased compared to before the intervention, indicating that the animation effectively supported learning. This study demonstrates that animated educational media can be an effective and practical tool for school health promotion, helping teachers deliver health messages in an engaging way and supporting early prevention of unhealthy eating habits among children.